Homotopy Perturbation Method for Time-Fractional Shock Wave Equation (Advances in Applied Mathematics and Mechanics, 2021)
A scheme is developed to study numerical solution of the time-fractionalshock wave equation and wave equation under initial conditions by the homotopyperturbation method (HPM). The fractional derivatives are taken in the Caputosense. The solutions are given in the form of series with easily computableterms. Numerical results are illustrated through the graph.